1965
DOI: 10.1083/jcb.26.3.857
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Formation of Protein Granules in the Fat Body of an Insect

Abstract: In the larva of the butterfly Calpodes ethlius, the fat body begins to store protein in the form of granules at about 30 to 35 hours before pupation, at a time when the endocuticle is being resorbed. At least two sorts of granule can be distinguished. The first granules to arise are those within vesicles of the Golgi complex. These may increase in size by incorporating material from microvesicles at their surface and by coalescence with one another. Later, at about 10 hours before pupation, another sort of gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
2

Year Published

1967
1967
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(86 citation statements)
references
References 11 publications
3
79
0
2
Order By: Relevance
“…At the end of the fifth larval intermolt, the fat body of a caterpillar switches from larval synthesis and secretion to storage for re-utilization during pupal and adult development (9,27,28,39,42,45). The switch involves the selective removal of organelles and is induced by β-ecdysone in vitro (10).…”
Section: Isolation Envelopes and Organelle-specific Turnover In Phagimentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the fifth larval intermolt, the fat body of a caterpillar switches from larval synthesis and secretion to storage for re-utilization during pupal and adult development (9,27,28,39,42,45). The switch involves the selective removal of organelles and is induced by β-ecdysone in vitro (10).…”
Section: Isolation Envelopes and Organelle-specific Turnover In Phagimentioning
confidence: 99%
“…Autophagic vacuoles, especially those in late stages containing RER, often fuse with endocytosed hemolymph protein to create mixed auto-and heterophagic vacuoles that go on to become storage granules. At the completion of autophagy, the fat body has been turned into a store for iron, protein, lipid, glycogen, and urate, everything needed for adult development (9,39,42,44).…”
Section: Organelle-specific Autophagymentioning
confidence: 99%
“…Locke and Collins (1965, 1966 demonstrated that both sequestration of haemolymph protein and lysis of cytoplasmic organelles contribute to the development of protein granules in Calpodes. Exogenous proteins, such as horseradish peroxidases, were taken up from the haemolymph into the granules at a time when the blood protein level was decreasing.…”
Section: (C) Relationship Of Plasma and Fat Body Proteinsmentioning
confidence: 99%
“…That thcsc vesiclcs which lack ribosomes cnter into the proximal pole of the Golgi apparatus, is a fact known from other plant cells (Grovc et al, 1966;1970), from arthropods (Lockc. 8: Collins, 1965;Ncwstead & Dornfcld, 1965;Phillips & Swift, 1965;Bcams C% Sckhon, 1966;Kcssel, 1966 a), from echinoderms (Kesscl, 1966b), from aniphibia (Pcrry 6; Waddington, 1966) and from mammals (Essncr & …”
Section: Discussionmentioning
confidence: 99%